Importance of Geo-informatics Professional Organizations of the World - Sharma, Rabin K (Journal on Geoinformatics, Nepal, 2017)
Development of sustainable system in Geo-informatics profession is guided by the professionalism which can be achieved by the professionals through participation in the events of Geo-informatics professional organizations. The professional organizations could be national, regional and international. Each of these organizations has their own objectives to disseminate information and data of research work carried out by the organizations and institutions around the globe. The organizations disseminate the information through different means and media. The professionals should try to acquire those information which will play a role to be benefitted the professionals, institutions and the country itself. So it is believed that professional organizations of the world play an important role for the technological development as well as for the development of professionalism. Nepalese Journal on Geoinformatics -13, 2014, Page: 1-6